The use of Traditional Medicine by Ghanaians in Canada - van Teijlingen Edwin R; Barimah Kofi B (BMC, 2008)
Abstract Background Research into health and health-care seeking behaviour amongst immigrant populations suggests that culturally-based behaviours change over time towards those prevalent in the host culture. Such acculturation of immigrant groups occurs as part of the interaction of immigrants with mainstream culture. This study examined the acculturation of Ghanaian immigrants in Greater Toronto Area (Canada) focusing particularly on attitudes towards and usage of Ghanaian traditional medicine (TRM). Methods The study used both quantitative and qualitative methods. Structured questionnaire interviews were conducted with a sample of Ghanaians in active collaboration with the Ghanaian-Canadian Association in the Greater Toronto Area (GTA). A total of 512 questionnaire interviews were conducted. In addition, three focus groups of nine participants each were conducted with a sub-sample of Ghanaians in Canada. Results Both the questionnaire and the focus groups indicated that nearly 73% of the Ghanaian immigrants in Canada have a positive attitude toward Ghanaian TRM. This is in comparison with less than 30% who have changed their attitude for various reasons. Some of the attraction of TRM lies in its holistic origin. Ghanaians in the GTA have been pursuing 'integration' and 'assimilation' in their acculturation in Canada. Some have given up or modified some of their attitudes and opinions toward TRM to embrace the 'modern' or 'civilized' way of living. Conclusion There is the need for health care providers and other stakeholders to be aware of the influence of religion on African immigrants during their acculturation process. Although modernity is said to be founded on the 'ruthless undermining of tradition', there is no evidence to suggest that Ghanaian traditional religion has been undermined to such an extent that there is a major change in attitudes towards TRM.